Implementation of Flipped Classroom in Students' Mathematical Problem Solving Ability - Rohmatulloh Rohmatulloh; Hepsi Nindiasari; Abdul Fatah (Jurnal Inovasi Matematika, 2022)
This research aims to determine the impact of flipped classroom learning models on students' problem-solving abilities. The research design used is a pseudo-experiment with a posttest-only control group. This study's population consisted of grade VIII students from SMP Serang for the 2021/2022 school year. Samples were determined using cluster random sampling techniques to obtain experimental and control classes. Data were gathered by administering a mathematical problem-solving ability test to students in the form of a description test at the end of the study. Based on posttest data, students' average mathematical problem-solving ability using a flipped classroom approach was 76.97 points. In comparison, students' average mathematical problem-solving ability using traditional learning was 64.33 points. The results of data analysis using a t-test with a 5% significance level revealed that the tcount is higher than ttable. This means that students who participate in flipped classroom learning have better problem-solving skills than students who use traditional learning models. As a result, flipped classroom model learning affects students' mathematical problem-solving abilities.